An approach to the historical development of female athletics in the Olympic Games - Mateos, C.; Molina, A. G.; Mosquera, M. S.; Vidal, A. M.; Patino, M. J. M. (Journal of Human Sport & Exercise, 2010)
This article will evolve around the subject of female integration and participation in athletics in the Olympic Games, analyzing the initial difficulties they encountered, the role played by sports institutions as well as international federations and the Olympic International Committee.